2020
DOI: 10.1073/pnas.2022788118
|View full text |Cite
|
Sign up to set email alerts
|

MdERDL6-mediated glucose efflux to the cytosol promotes sugar accumulation in the vacuole through up-regulating TSTs in apple and tomato

Abstract: Sugar transport across tonoplasts is essential for maintaining cellular sugar homeostasis and metabolic balance in plant cells. It remains unclear, however, how this process is regulated among different classes of sugar transporters. Here, we identified a tonoplast H+/glucose symporter, MdERDL6-1, from apples, which was highly expressed in fruits and exhibited expression patterns similar to those of the tonoplast H+/sugar antiporters MdTST1 and MdTST2. Overexpression ofMdERDL6-1unexpectedly increased not only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 53 publications
3
79
0
Order By: Relevance
“…17 ), so it was designated as PpERDL16 . Previous studies showed that AtERDL6 in Arabidopsis and MdERDL6-1 in apple are symporter proteins that function in glucose export from the vacuole into the cytosol 69 , 70 , and transgenic Arabidopsis lines overexpressing AtERDL6 showed lower levels of glucose and fructose in leaves as compared to wild type plants 69 . We confirmed the tonoplast localization of the PpERDL16-GFP fusion protein in tobacco leaf cells using the Atγ-TIP-mCherry fusion protein as the positive control (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…17 ), so it was designated as PpERDL16 . Previous studies showed that AtERDL6 in Arabidopsis and MdERDL6-1 in apple are symporter proteins that function in glucose export from the vacuole into the cytosol 69 , 70 , and transgenic Arabidopsis lines overexpressing AtERDL6 showed lower levels of glucose and fructose in leaves as compared to wild type plants 69 . We confirmed the tonoplast localization of the PpERDL16-GFP fusion protein in tobacco leaf cells using the Atγ-TIP-mCherry fusion protein as the positive control (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is highly expressed in fruits, and its encoded protein seems to be localized on the tonoplast, where it acts as a low-affinity H + /glucose symporter. In an inverse relation to AtERDL6, the overexpression of MdERDL6-1 in apple and tomato leaves and fruits leads to an increase rather than a decrease in sugar levels (Zhu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The TST family genes are involved in vacuolar sugar accumulation in different species, such as Arabidopsis (Schulz et al, 2011; Wormit et al, 2006), sugar beet (Jung et al, 2015), tomato and apple (Zhu et al, 2021). However, none of the previously identified TST genes are stem‐specifically expressed.…”
Section: Discussionmentioning
confidence: 99%